Substrate for drug solution impregnation

By using specific proportions of bonded fibers and high melting point fibers in the paper, the problems of slow production speed and insufficient absorption in the prior art are solved, and efficient chemical liquid absorption and low damage rate paper manufacturing are achieved.

JP2025018617APending Publication Date: 2025-02-06NIPPON PAPER PAPYLIA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023122486
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

The existing chemical liquid adsorbent materials have problems such as slow production speed, insufficient absorption rate and easy to break during the production process, especially when the chemical liquid impregnation process is prone to paper cutting and machine debris.

Method used

It adopts a single-layer or multi-layer paper structure, containing 10-80% bonded fibers and high melting point fibers. The bonded fibers are core cortical polyester fibers, with a high melting point fiber content of no more than 20%. It is manufactured by a paper machine, and the base weight and density are controlled within a specific range to ensure high absorption and strength.

Benefits of technology

The rapid absorption of chemical liquids and low breakage rate are achieved, the production efficiency is improved, and the damage of paper during the manufacturing and impregnation process is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018617000001
    Figure 2025018617000001
Patent Text Reader

Abstract

To provide a substrate for drug solution impregnation that enables fast absorption of drug solution while preventing breakage during production.SOLUTION: A substrate for drug solution impregnation is single-layer or multi-layer paper, comprising natural fibers and binder fibers as papermaking fibers. Relative to the total amount of the papermaking fibers, the binder fibers are contained by 10 wt.% or more and 80 wt.% or less. The substrate has a paper layer where the total freeness of the natural fibers is 570 ml or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a substrate for impregnation with a chemical solution, which is used for impregnating and retaining a volatile chemical and releasing it into the air at room temperature, and more specifically, to a substrate for impregnation with a chemical solution, which has excellent liquid absorption properties for chemical solutions for the purposes of killing insects, sterilizing, controlling insects, repelling pests, providing fragrance, deodorizing, and the like. [Background technology]

[0002] Substrates for impregnating chemical solutions are used in suction-type liquid air fresheners and deodorants, where the chemical solution in the container is sucked up and replenished into the substrate while the chemical volatilizes from the substrate into the atmosphere, and as indicators to show the effective period of insect repellents, deodorants, etc. The indicator is configured to display a message indicating the end of the effective period as the amount of the chemical solution decreases due to evaporation. When an indicator function is imparted to a chemical solution-impregnated substrate, the chemical solution is not supplied over time, and therefore, in order to achieve the target chemical solution effect and the effective period of the indicator function, various proposals have been made regarding the liquid absorption performance of the chemical solution-impregnated substrate and the imparting of the indicator function.

[0003] Patent Document 1 describes a papermaking method that contains both mercerized pulp and non-mercerized pulp, in which the blending ratio of non-mercerized pulp is 30 to 90 mass %, and the density is 0.30 to 0.38 g / cm 3 , A base paper with an internal bond strength of 50 mJ or more has been proposed. It is explained that the use of mercerized pulp results in a base paper with high bulk, low density, and high chemical impregnation rate. Patent Document 2 describes a chemical-impregnated substrate having a first layer and a third layer mainly made of cellulose fibers and a second layer made of cellulose fibers and synthetic fibers laminated between them, which has a chemical-impregnated substrate surface that has good absorbency and diffusibility when a chemical solution is dropped onto the surface of the chemical-impregnated substrate to impregnate the substrate. The chemical-impregnated substrate has a cellulose fiber / synthetic fiber blending ratio of 20-80:80-20% by weight in the second layer, the cellulose fiber contains at least 50% by weight or more of mercerized pulp or cotton linter pulp, the synthetic fiber is made of main fiber and binder fiber, the main fiber / binder fiber blending ratio is 20-80:80-20% by weight, the first layer, the second layer, and the third layer have a layer ratio of 45-35:30-10:45-35% by weight, and the chemical-impregnated substrate has a basis weight of 75-500 g / m 2 , and density is 0.25~0.50g / cm 3 It has been proposed that However, in terms of productivity in the chemical impregnation process, there is a demand for further improvement in production speed, and the absorption speed of the chemical solution in the substrate proposed by these methods is insufficient. If the density of the substrate is further reduced in order to increase the absorption speed of the chemical solution, the substrate will break during the chemical impregnation process due to insufficient strength of the substrate. There is a demand for a substrate that has the strength required for the production process and has an improved absorption speed of the chemical solution. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-168514 A [Patent Document 2] JP 2015-193954 A Summary of the Invention [Problem to be solved by the invention]

[0005] In the past, the use of mercerized pulp and cotton linters has been proposed for use in chemical-impregnated substrates (hereinafter also referred to as substrates) used in indicators and the like impregnated with chemicals, in the face of demands for improved productivity. However, these proposed substrates are insufficient for the required absorption speed of chemicals, and improvements have been required. In addition, the approach of reducing the density of the substrate to improve chemical impregnation was not a desirable measure because it would lead to deterioration of operability due to the occurrence of paper breaks and machine stains during the papermaking process, and would significantly cause breakage of the substrate during the chemical impregnation process. An object of the present invention is to provide a substrate for chemical solution impregnation that quickly absorbs a chemical solution and is less likely to break during production. [Means for solving the problem]

[0006] The means for solving the problems of the present invention are as follows. 1. It is a single-ply or multi-ply paper, The papermaking fibers include natural fibers and binder fibers, The binder fiber is contained in an amount of 10% by weight or more and 80% by weight or less based on the total papermaking fibers, A chemical solution impregnated substrate comprising a paper layer having a total freeness of the natural fibers of 570 ml or more. 2. The chemical solution-impregnated substrate according to 1., further comprising high-melting-point fibers as papermaking fibers, the content of said high-melting-point fibers being 20% ​​by weight or less based on the total papermaking fibers. 3. The chemical solution-impregnated substrate according to 1 or 2, wherein the binder fiber is a core-sheath polyester fiber. 4. Grammage: 120g / m 2 and the density is 0.55g / cm 3 4. The chemical solution-impregnated substrate according to any one of 1. to 3., characterized in that: 5. The substrate for chemical liquid impregnation according to any one of 1. to 4., characterized in that the tensile strength measured according to JIS P8113 is 2.0 kN / m or more, and the wet tensile strength measured according to JIS P8135 is 0.4 kN / m or more. Effect of the Invention

[0007] According to the present invention, it is possible to provide a substrate for chemical liquid impregnation, which has a high chemical liquid impregnation rate and is less likely to break during the chemical liquid impregnation step. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Chemical impregnation substrate The substrate for chemical solution impregnation of the present invention is a single-ply or multi-ply paper, has at least one paper layer made from a slurry containing natural fibers and binder fibers adjusted to a target freeness as a papermaking raw material, and can be manufactured using a papermaking machine used in known papermaking applications.

[0009] (Natural Fibers) The natural fibers include wood pulps such as coniferous pulp and hardwood pulp, bast fibers such as flax, ramie, jute, kenaf, hemp, paper mulberry, and mitsumata, hard fibers such as bagasse, bamboo, and esparto, seed hair fibers such as cotton pulp, and non-wood pulps such as leaf sheath and leaf fibers such as abaca and sisal, and one or more of these can be used. Note that the hemp pulp that can be used is flax, ramie, jute, kenaf, hemp, abaca, sisal, etc. As the natural fibers used in the present invention, hemp pulp or softwood pulp, which has relatively long fiber length, is preferably used to ensure the wet strength and air permeability required for the base material, and these may be used in combination. When using natural fibers such as hemp pulp and softwood pulp, each natural fiber may be beaten separately and then mixed, or multiple natural fibers may be mixed and beaten (called mixed beating) before use.

[0010] The total freeness of the natural fiber is 570 ml or more. The total freeness is the Canadian standard freeness measured according to JIS P8121-2:2012, and when two or more types of natural fibers are mixed, it is the freeness after mixing the natural fibers in a specified ratio. A base material made from natural fibers beaten to a total freeness of less than 570 ml may not achieve the target chemical impregnation speed because it is difficult to reduce the density and the voids in the base material become small. The total freeness of the natural fiber is preferably 600 ml or more, and more preferably 650 ml or more. If the total freeness exceeds 800 ml, the tensile strength decreases, which may cause paper breakage during the papermaking process, or even if the paper can be made, the wet strength decreases and the base material may break during the chemical impregnation process.

[0011] (binder fiber) When the base material is made into paper, the binder fibers melt due to the heat and pressure applied in the dryer section, forming bonding points between natural fibers or between natural fibers and any other papermaking fibers. Therefore, the strength of the base material can be maintained even when natural fibers with a low degree of beating or high melting point fibers that do not form bonding points due to melting are used to increase liquid absorption. As the binder fiber, composite fibers such as core-sheath type, eccentric type, side-by-side type, or single component type can be used, but the use of core-sheath type composite fibers is preferred. Examples of such core-sheath type composite fibers include combinations of polyester resin-polyester copolymer resin, polyester resin-polyethylene resin, polyester resin-ethylene-vinyl alcohol copolymer resin, polypropylene resin-polyester copolymer resin, polypropylene resin-polyethylene resin, polypropylene resin-ethylene-vinyl alcohol copolymer resin, polypropylene resin-ethylene-vinyl acetate copolymer resin, polypropylene resin-polyethylene-propylene copolymer resin, etc. as the core-sheath component, but the above-mentioned examples are not limited to the above examples, and any core-sheath type composite binder fiber can be used as long as the resin used in the sheath has a lower melting point or a lower crystallinity than the resin used in the core and is fused by heat and / or pressure.

[0012] The amount of binder fiber to be mixed with the total fibers for papermaking is 10% by weight or more and 80% by weight or less. If the amount of binder fiber is less than 10% by weight, the number of bonding points with natural fibers or high melting point fibers, etc. will be reduced, and the tensile strength will be weakened, which may cause the paper to break during papermaking. Furthermore, even if the paper can be made, the wet tensile strength will be reduced, which may cause the base material to break during the chemical impregnation process. Also, if the amount of binder fiber is more than 80% by weight, the base material sheet may stick to the drying roll due to melting in the dryer part during the papermaking process, causing the paper to break.

[0013] (High melting point fiber) In order to complement the decrease in liquid absorption caused by the decrease in freeness of natural fibers, high melting point fibers can be used in combination. A high melting point fiber is a fiber with a melting point of 150°C or higher, and can maintain its fiber shape without melting during the drying process during papermaking. A high melting point fiber is any papermaking fiber that can be blended as needed, but since high melting point fibers do not melt or soften under the heating and pressure treatment conditions during papermaking, the desired density can be obtained without reducing the strength of the base material made by blending high melting point fibers. In other words, the deterioration of liquid absorption when using natural fibers that have been beaten by blending high melting point fibers can be complemented. When high melting point fibers are used in combination, the blending amount is preferably 20% by weight or less of the total papermaking fibers. If the blending amount of high melting point fibers exceeds 20% by weight, the tensile strength may be inferior.

[0014] The melting point of the high melting point fiber is preferably 160° C. or higher, more preferably 180° C. or higher, and even more preferably 200° C. or higher. The type of high melting point fiber is not particularly limited, and one or more of mainly polyester fibers (PET fibers), mainly polypropylene fibers (PP fibers), polyphenylene sulfide fibers (PPS fibers), rayon fibers, etc. may be arbitrarily blended, but mainly polyester fibers are preferred in consideration of the selectivity of fiber length and fineness for quality adjustment and machine soiling in the papermaking process.

[0015] The substrate of the present invention may be a single-ply paper or a multi-ply paper. In the case of a multi-ply paper, at least one paper layer contains natural fibers and synthetic fibers as papermaking fibers, and the synthetic fibers are contained in an amount of 20% by weight or more and 80% by weight or less relative to the papermaking fibers, and the synthetic fibers contain high melting point fibers and binder fibers in a weight ratio of 20-70:80-30. In the case of a multi-ply paper, the paper materials constituting each paper layer may be the same or different, but it is preferable that all paper layers satisfy the above-mentioned specific composition.

[0016] The basis weight of the base material is 120 g / m 2 The basis weight is preferably 120 g / m or more. 2 If it is less than this, the wet tensile strength may decrease, causing breakage during the liquid absorption process, or the desired amount of liquid absorption may not be achieved. 2 More than 180g / m is preferable. 2 At higher basis weights, the volatility of the absorbed chemical solution may deteriorate, and the effect of chemical solution volatilization may decrease. Therefore, it is preferable to adjust the upper limit of the basis weight as appropriate, taking into account costs, the chemical solution to be used, and the target usage period (volatility). The density of the substrate is 0.55 g / cm 3 A basis weight of 0.55 g / cm is preferred. 3 If it exceeds this value, the voids will be small and the amount of chemical solution absorbed may be insufficient. In addition, the density of the base material should be 0.28 g / cm3 from the viewpoint of wet tensile strength. 3 The above is preferred.

[0017] The strength of the paper base material is preferably 2.0 kN / m or more, more preferably 2.5 kN / m or more, in terms of dry tensile strength in the machine direction measured in accordance with JIS P8113. If the dry tensile strength is less than 2.0 kN / m, paper breaks may occur during the papermaking process. The strength of the paper base material is preferably 0.4 kN / m or more, more preferably 0.5 kN / m or more, in terms of wet tensile strength measured according to JIS P8135. If the wet tensile strength is less than 0.4 kN / m, the paper may break during the chemical impregnation step, making it impossible to impregnate the chemical, and it may be necessary to sacrifice work efficiency and use a dispensing device or the like.

[0018] (Manufacturing method) The chemical solution-impregnated substrate of the present invention can be manufactured by a method used in known papermaking applications. Specifically, it can be manufactured by using a fourdrinier paper machine, a cylinder paper machine, a short wire paper machine, a twin-wire paper machine, an on-top hybrid paper machine, a gap former machine, or the like, or a multi-layer paper machine that combines these. Additives can also be added as necessary. For example, fillers, pigments, sizing agents, coagulants, fluorescent whitening agents, aluminum sulfate, retention aids, drainage aids, dry strength agents, wet strength agents, coloring dyes, coloring pigments, water resistance agents, etc. can be used alone or in combination. These additives are preferably added internally, but can also be added (externally) by impregnation processing using a mangle, size press, etc., or surface coating using a gate roll coater, blade coater, bar coater, gravure coater, die coater, curtain coater, spray coater, etc. EXAMPLES

[0019] Example 1 A papermaking stock was prepared by mixing and stirring 65.0% by weight of mercerized NBKP (NBKP1) with a Canadian Standard Freeness (CSF) of 760 ml and 35.0% by weight of binder fiber (core-sheath PET binder fiber, 2.2 dtex × 5 mm, melting point 110°C; manufactured by Teijin Limited). Using this papermaking stock, a target basis weight of 150 g / m was obtained. 2 The wet paper was dried at 120° C. for 2 minutes to obtain a substrate.

[0020] Example 2 The papermaking raw material was prepared by mixing and stirring NBKP1 at 75.0% by weight and binder fiber at 25.0% by weight. This papermaking raw material was used to prepare a papermaking raw material with a target basis weight of 150 g / m 2 The wet paper was dried at 120° C. for 2 minutes to obtain a substrate. Example 3 The raw materials for papermaking were prepared by mixing and stirring 51.0% by weight of NBKP1, 24.0% by weight of NBKP (NBKP2) with a Canadian Standard Freeness (CSF) of 653 ml, and 25.0% by weight of binder fiber, and papermaking was carried out in the same manner as in Example 1 to obtain a base material.

[0021] Example 4 The mixture was stirred to prepare a papermaking raw material containing 53.5% by weight of NBKP1, 28.0% by weight of NBKP2, and 18.5% by weight of binder fiber, and papermaking was carried out in the same manner as in Example 1 to obtain a base material. Example 5 The papermaking raw materials were prepared by mixing and stirring 41.6% by weight of NBKP1, 30.1% by weight of NBKP2, 15.0% by weight of high melting point fiber (mainly PET fiber, 3.3 dtex × 5 mm, melting point 260°C; manufactured by Teijin Limited), and 13.3% by weight of binder fiber, and papermaking was performed in the same manner as in Example 1 to obtain a substrate.

[0022] Comparative Example 1 NBKP1 was 62.5% by weight, NBKP2 was 29.5% by weight, and binder fiber was 8.0% by weight. The mixture was mixed and stirred to prepare a papermaking raw material, and papermaking was carried out in the same manner as in Example 1 to obtain a base material. Comparative Example 2 The raw materials for papermaking were prepared by mixing and stirring 30.5% by weight of NBKP2, 41.2% by weight of LBKP with Canadian Standard Freeness (CSF) of 500 ml, and 25.3% by weight of binder fiber, and papermaking was carried out in the same manner as in Example 1 to obtain a substrate.

[0023] Comparative Example 3 NBKP1 was 38.7% by weight, NBKP2 was 28.0% by weight, and the high melting point fiber was 33.3% by weight. The mixture was stirred to prepare a papermaking raw material, and papermaking was carried out in the same manner as in Example 1 to obtain a base material. Comparative Example 4 The mixture was stirred so that NBKP1 was 58.0% by weight and NBKP2 was 42.0% by weight to prepare a raw material for papermaking. The mixture was then subjected to papermaking in the same manner as in Example 1 to obtain a base material.

[0024] (Evaluation method) (1) Overall freeness Canadian standard freeness was measured according to JIS P8121-2:2012. (2)Basic weight Measurements were performed in accordance with JIS P8124. (3) Thickness Measurements were performed in accordance with JIS P8118. (4) Density Calculated from basis weight and thickness values.

[0025] (5) Dry tensile strength Measurements were performed in accordance with JIS P8113:2006. The dry tensile strength was evaluated as "good, fair, or bad" as follows. If the evaluation was good or fair, there was no problem in practical use. "〇": 2.5kN / m or more "△": 2.0kN / m or more and less than 2.5kN / m "×": Less than 2.0kN / m (6) Wet tensile strength Measurements were performed in accordance with JIS P8135:1998. If the wet tensile strength falls below 0.4 kN / m, the paper may break during the impregnation process. Therefore, when the value was equal to or greater than this value, it was evaluated as "good", and when the value was less than this value, it was evaluated as "bad".

[0026] (7)Liquid absorption The measurement sample was conditioned for 24 hours in an atmosphere of 23°C and 50% RH, and a test piece (5cm x 10cm) was prepared from this sample. 40μl of the pyrethroid compound profluthrin (trade name: Fairtail (viscosity 14.1mPa·s) / manufactured by Sumitomo Chemical Co., Ltd.) was dropped onto the measurement surface of the test piece using a microsyringe, and the time until the drug penetrated the sample (liquid absorption time) was measured using a dynamic contact angle absorption tester (FIBRO 1100 DAT MKII: manufactured by FIBRO System AB). The liquid absorption was evaluated based on this liquid absorption time as follows, with a "good" or "bad" rating. "〇": Less than 12 seconds "×": 12 seconds or more

[0027] [Table 1]

[0028] ·result The chemical solution-impregnated substrates obtained in Examples 1 to 5 were less susceptible to breakage during production and had excellent liquid absorbency. The chemical solution-impregnated substrate obtained in Comparative Example 1 had excellent liquid absorbency, but was insufficient in strength due to the small amount of binder fiber blended. The chemical solution-impregnated substrate obtained in Comparative Example 2 had sufficient strength to prevent breakage during production, but the natural fibers were highly beaten, so the gaps between the fibers were small and the liquid absorbency was poor. The chemical solution-impregnated substrate obtained in Comparative Example 3 was inferior in strength since it did not contain binder fibers. The chemical solution-impregnated substrate obtained in Comparative Example 4 was made only of natural fibers, and therefore had poor strength when wet and also poor liquid absorbency.

Claims

1. It is a single-ply or multi-ply paper, The papermaking fibers include natural fibers and binder fibers, The binder fiber is contained in an amount of 10% by weight or more and 80% by weight or less based on the total papermaking fibers, A chemical solution impregnated substrate comprising a paper layer having a total freeness of the natural fibers of 570 ml or more.

2. 2. The chemical solution-impregnated substrate according to claim 1, further comprising high-melting-point fibers as papermaking fibers, the content of said high-melting-point fibers being 20% ​​by weight or less based on the total papermaking fibers.

3. 3. The chemical solution-impregnated substrate according to claim 1, wherein the binder fiber is a core-sheath polyester fiber.

4. Basis weight: 120 g / m 2 or more, and the density is 0.55 g / cm 3 3. The chemical solution-impregnated substrate according to claim 1, wherein the chemical solution-impregnated substrate is one of the following:

5. 3. The chemical solution-impregnated substrate according to claim 1, wherein the tensile strength measured according to JIS P8113 is 2.0 kN / m or more, and the wet tensile strength measured according to JIS P8135 is 0.4 kN / m or more.

Citation Information

Patent Citations

  • Chemical-impregnation base material

    JP2015193954A

  • Chemical liquid-impregnated substrate and production method thereof

    JP2018168514A